2017
DOI: 10.1016/j.renene.2017.05.091
|View full text |Cite
|
Sign up to set email alerts
|

Battery sizing for PV power plants under regulations using randomized algorithms

Abstract: International audienceThe increasing amount of PV (photovoltaic) power plants comes along with an increased instability in the power grid due to the high uncertainty of the PV power production. As a stabilizing measure, grid operators introduce regulations on the injected power profiles comprising the obligation to declare in advance the predicted power production as well as penal- ties which apply in case these previously declared production profiles were not respected. In order to meet these regulations powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Fluctuations in the generation of PV power were addressed using an optimization strategy to determine the most effective battery size. A randomized algorithm was used to increase the revenue of the PV/BESS [41]. There is no universal solution because of differing environmental conditions and electricity prices in different regions.…”
Section: B Optimization Schemes Based On Maximization Of Supply Side ...mentioning
confidence: 99%
“…Fluctuations in the generation of PV power were addressed using an optimization strategy to determine the most effective battery size. A randomized algorithm was used to increase the revenue of the PV/BESS [41]. There is no universal solution because of differing environmental conditions and electricity prices in different regions.…”
Section: B Optimization Schemes Based On Maximization Of Supply Side ...mentioning
confidence: 99%
“…Additionally, it is worth mentioning that PV power generation and load demand time series profile including longer time periods (e.g., years) are not always accessible. For that reason, short time periods examining specific set of operating conditions are often considered in the sizing procedure [14]. However, current industry requirements imply fast and accurate solutions in the sizing process covering a large spectrum of operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A notable decrease in the PV system price in addition to an increase the fossil fuel price that encourage people to use the PV systems as a source of energy. Accordingly, a mismatch between the customers and the utility side had been occurred, and it was found that the integration of the battery storage systems is one of the best solutions to fill the gap between the customers and the utility 1 . There are many economic factors that can be used to evaluate the benefits of installing PV and battery storage systems 2 .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Accordingly, a mismatch between the customers and the utility side had been occurred, and it was found that the integration of the battery storage systems is one of the best solutions to fill the gap between the customers and the utility. 1 There are many economic factors that can be used to evaluate the benefits of installing PV and battery storage systems. 2 These factors like levelized cost of energy (LCOE), net present value (NPV), payback period, and electricity bill saving, which can determine the economic viability of the system.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%